2014
DOI: 10.1001/jama.2014.3740
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PET Before Liver Resection on Surgical Management for Colorectal Adenocarcinoma Metastases

Abstract: clinicaltrials.gov Identifier: NCT00265356.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(92 citation statements)
references
References 25 publications
6
84
1
1
Order By: Relevance
“…The authors demonstrated that PET/CT changed the treatment plan to curative intent in 37% patients, and there was a statistically significant (P 5 0.004) difference in the median progression-free survival and OS (P 5 0.045) between patients planned to receive curative treatment before and after the PET/CT study (5). In a study by Moulton et al of 263 patients with colorectal cancer treated by surgical resection and who had resectable colorectal liver metastasis, there was change in management in 8.0% patients who underwent a PET/CT study (21). In our study, there was change in management after 34.2% of the fourth and subsequent follow-up PET/CT scans.…”
Section: Discussionsupporting
confidence: 43%
“…The authors demonstrated that PET/CT changed the treatment plan to curative intent in 37% patients, and there was a statistically significant (P 5 0.004) difference in the median progression-free survival and OS (P 5 0.045) between patients planned to receive curative treatment before and after the PET/CT study (5). In a study by Moulton et al of 263 patients with colorectal cancer treated by surgical resection and who had resectable colorectal liver metastasis, there was change in management in 8.0% patients who underwent a PET/CT study (21). In our study, there was change in management after 34.2% of the fourth and subsequent follow-up PET/CT scans.…”
Section: Discussionsupporting
confidence: 43%
“…In an RCT of patients with resectable CRCLM (not specifically synchronous), the use of PET-CT compared with CT alone did not result in significant changes in surgical management [27]. A role [12]: A, recommendation based on consistent and good-quality patient-oriented evidence; B, recommendation based on inconsistent or limited-quality patient-oriented evidence; C, recommendation based on consensus, usual practice, opinion, disease-oriented evidence or case series for studies of diagnosis, treatment, prevention or screening.…”
Section: The Role Of Imaging In the Detection Of Synchronous Crclmmentioning
confidence: 95%
“…One scenario in particular that may be amenable to PET/CT evaluation is exclusion of occult metastases in patients being considered for liver metastectomy with curative intent (26). In a recent randomized controlled trial (42) in which the effect of preoperative PET/CT was compared with that of standard CT in surgical treatment of resectable hepatic metastases, the authors found that 8% of patients had a change in surgical treatment plan after FDG PET, but the effect on overall survival was not statistically significant. PET/CT also outperforms contrastenhanced CT for detection of extrahepatic metastatic disease (43).…”
Section: Initial Assessment Rectal Cancermentioning
confidence: 99%